Réponses

2013-11-24T15:53:19+01:00
A) P(ABCD) = 4x + 3x + 12x + 13x

b) P(EFGH) = 2(10x) + 2(6x)

c) P(ABCD) =  32x
    P(EFGH) = 20x + 12x
    P(EFGH) = 32x

Donc P(ABCD) = P(EFGH)

d) P(ABCD) = 25.6
            32x = 25.6
        32x/32 = 25.6/32
                x = 0.8

e) A(ABCD) = [(12 x 0.8) x ( 5 x 0.8) /2]  + [( 3 x 0.8) x ( 4 x 0.8) /2]
                  = [ (9.6 x 4) /2]  +  [ (2.4 x 3.2) /2]
                  = (38.4 /2) + ( 7.68/2)
                  = 19.2 + 3.84
                  = 23.04 cm

f) P(EFGH) = 32 x 0.8         si x = 0.8cm car on sait que P(EFGH) = 32x
                 =  25.6 cm                                                                 = (32) x ( x)
 

Et voila ^^ !!